Inactivation Mechanism of Escherichia coli Induced by Slightly Acidic Electrolyzed Water - Zhangying Ye (Nature Portfolio, 2017)
Abstract Foodborne disease outbreak caused by food microbiological contamination is a serious public health problem. Slightly acidic electrolyzed water (SAEW), a new ultra-high effect and wide-spectrum disinfectant that is colourless, odourless, and harmless to humans and the environment, is directly used on food surfaces in Japan and America. However, the underlying inactivation mechanism remains unknown. In this study, biochemical and cellular changes were observed to investigate the bactericidal mechanism of SAEW against Escherichia coli (E. coli). The results indicated that SAEW with a pH of 6.40, an oxidation-reduction potential (ORP) of 910 mV, an available chlorine concentration (ACC) of 60 mg/L, and a volume ratio of 20:1, produced the most effective sterilization action. A fluorescence-based live-dead assay was further used to demonstrate the sterilized effect and the cell esterase activity damage caused by SAEW. During the observation period, within 10 min, the cell morphology changed, which was characterized by cell expansion, cell elongation and increased membrane permeability. Meanwhile, reactive oxygen substances (ROS) were released in the bacterial cells. E. coli inactivation and apoptosis induced by SAEW were observed. Our findings illustrate that the bactericidal effects of SAEW against E. coli occurred through cellular and biochemical mechanisms of cell necrosis and apoptosis.